2021
DOI: 10.3390/atmos12040444
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the VLF Signal Phase Noise Before Earthquakes

Abstract: In this paper we analyse temporal variations of the phase of a very low frequency (VLF) signal, used for the lower ionosphere monitoring, in periods around four earthquakes (EQs) with magnitude greater than 4. We provide two analyses in time and frequency domains. First, we analyse time evolution of the phase noise. And second, we examine variations of the frequency spectrum using Fast Fourier Transform (FFT) in order to detect hydrodynamic wave excitations and attenuations. This study follows a previous inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 45 publications
3
23
1
Order By: Relevance
“…The presented analysis of the noise amplitude in a localized area during PISA is a pioneer study and the confirmation of the obtained conclusions requires additional case studies or statistical research which should be carried out in future. However, a comparison of the study of the VLF signal characteristics related to separated relatively strong EQs given in Nina et al (2020) and Nina et al (2021a) indicates similarities with conclusions obtained in this study for the corresponding periods. The potential horizontal displacements and enlargements of the area related to the seismic zone indicated in this study are also shown in the studies of the atmospheric chemical potential (ACP) and TEC.…”
Section: Comparisons With Other Studiessupporting
confidence: 82%
See 3 more Smart Citations
“…The presented analysis of the noise amplitude in a localized area during PISA is a pioneer study and the confirmation of the obtained conclusions requires additional case studies or statistical research which should be carried out in future. However, a comparison of the study of the VLF signal characteristics related to separated relatively strong EQs given in Nina et al (2020) and Nina et al (2021a) indicates similarities with conclusions obtained in this study for the corresponding periods. The potential horizontal displacements and enlargements of the area related to the seismic zone indicated in this study are also shown in the studies of the atmospheric chemical potential (ACP) and TEC.…”
Section: Comparisons With Other Studiessupporting
confidence: 82%
“…The procedure for the determination of the noise amplitude, A noise , used in this study is described in Nina et al (2015) and applied in the studies of the noise reductions in the amplitude and phase presented in Nina et al (2020) and Nina et al (2021a), respectively. It is based on processing of the signal amplitude A recorded by the AbsPAL receiver with time resolution of 0.1 s, and on determining of:…”
Section: Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Those precursors are primarily associated with changes in the VLF signal amplitude and/or phase [1][2][3][4][5] and the amplitude minimum time shift during solar terminator periods (the so-called "terminator time") [6][7][8][9][10]. In addition, the most recent research suggests that there are reductions in the noise of the VLF signal amplitude and phase a few tens of minutes before the observed type of disaster [11][12][13]. Although various data processing procedures have been applied in previous studies, there is still no way to reliably predict an earthquake.…”
Section: Introductionmentioning
confidence: 99%